Young Adults’ Evolving Values, Attitudes, Behavior, and Processes of Unlearning in a Post-Pandemic World - Adrianne Mateo; Inero Ancho; Rufo Gil Albor; Sarah Jen Paccarangan; Daisy Pelegrina; Phrygian Almeda (Indonesian Journal of Behavioral Studies, 2025)
Young adults' beliefs, attitudes, and perspectives on life were profoundly shaped by the COVID-19 pandemic, which disrupted their developmental transitions and reshaped their personal, social, and professional lives. This study aims to explore the specific changes in values, attitudes, and belief systems that emerged among young adults during the pandemic, examine their positive and negative effects in the post-pandemic context, and investigate young adults’ willingness to unlearn behaviors and perceptions acquired during this period. This qualitative phenomenological study involved semi-structured interviews with ten young adults who either entered college or joined the workforce during the height of the pandemic, capturing their lived experiences of adaptation and change. Thematic analysis revealed several key insights: participants experienced a re-emphasis on core values such as family, health, and time; developed coping mechanisms that included financial prudence and digital reliance; and expressed varied levels of willingness to unlearn maladaptive behaviors such as social withdrawal and overuse of digital platforms. These findings suggest that adaptation among young adults is not merely behavioral but involves conscious reflection and restructuring of beliefs and routines. The study contributes to understanding how crises affect the developmental trajectories of emerging adults and emphasizes the role of unlearning in navigating post-pandemic transitions.